2012
DOI: 10.1158/0008-5472.can-11-2505
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid/Alpha-Interferon Combination Inhibits Growth and Promotes Apoptosis in Mantle Cell Lymphoma through Akt-Dependent Modulation of Critical Targets

Abstract: Mantle cell lymphoma (MCL) is characterized by a profound deregulation of the mechanisms controlling cell-cycle progression and survival. We herein show that the combination of 9-cis-retinoic acid (RA) and IFN-a induces marked antiproliferative and proapoptotic effects in MCL cells through the modulation of critical targets. Particularly, IFN-a enhances RA-mediated G 0 -G 1 cell accumulation by downregulating cyclin D1 and increasing p27Kip1 and p21 WAF1/Cip1 protein levels. Furthermore, RA/IFN-a combination a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Previously, we demonstrated that RA/IFN-α treatment induces apoptosis in MCL cells through the inhibition of the PI3-K/Akt pathway [24]. Given the significance of this signalling in the cross-talk between apoptosis and autophagy [31, 32], we investigated the possible relationship between RA/IFN-α-induced cell death and autophagy in MCL cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we demonstrated that RA/IFN-α treatment induces apoptosis in MCL cells through the inhibition of the PI3-K/Akt pathway [24]. Given the significance of this signalling in the cross-talk between apoptosis and autophagy [31, 32], we investigated the possible relationship between RA/IFN-α-induced cell death and autophagy in MCL cells.…”
Section: Resultsmentioning
confidence: 99%
“…Aiming at this goal, we have exploited the features of MCL cell apoptosis induced by the combination of 9- cis -retinoic acid (RA) and Interferon(IFN)-α [24], two drugs that may stimulate both pro-apoptotic and autophagic effects in different cellular backgrounds, including lymphocytes [25, 26]. In particular, gene expression profiling approach identified phospholipid scramblase 1 (PLSCR1) as one of the pro-apoptotic genes significantly up-regulated by RA/IFN-α treatment in different MCL cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…The A c c e p t e d M a n u s c r i p t elevation and it is associated with cell-cycle arrest (9,35,36) . Our study, for the first time, demonstrated that the negative correlation between VRK1 and p27 kip1 expression might be the reason for cell cycle arrest and CAM-DR in MM cells.…”
Section: Discussionmentioning
confidence: 99%
“…Both EGCG and retinoids have been demonstrated to activate Foxo3a: in Trastuzumab-resistant HER2-driven breast cancer cells [49] and in ER α -positive breast cancer cells [50] the activation of Foxo3a by EGCG played an important role in the resulting cytotoxicity: all samples treated with EGCG + IIF and IIF alone for 24 h showed a significant increase in Foxo3a RNA expression. Retinoids could switch Foxo3a to the nucleus and trigger apoptosis: Foxo3a is a key molecule in ATRA action on acute promyelocytic leukaemia cells [51] as well as RA and IFN- α in mantle cell lymphoma [52]. The different mechanisms underlying Foxo3a activation might be related to the different biomolecular characteristics of MCF-7, MCF-7TAM, and MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 99%